THE ROLE OF NEUROPSYCHOPEDAGOGY IN INCLUSIVE EDUCATION WITHIN THE SCHOOL CONTEXT - Vieira da Silva, Gracilene (Revista Gênero e Interdisciplinaridade, 2024)
The current article, entitled The role of neuropsychopedagogy in inclusive education within the school context, has as its primary objective the examination of the work developed by Neurosciences and how they can collaborate or intervene through their neuropsychopedagogical knowledge in an educational institution. Hoping that means can be found that appropriately prove information that triggers obstacles in learning, knowing that the cause of this problem may be based on the various types of biopsycho and socio-familial disorders. Believing that every practical action of the school must provide an effective interaction of the student and, by understanding education as the only reason for the improvement of the human being and society, it is at this moment that the Neuropsychopedagogy professional begins to obtain a primary role in the approach and elucidation of the blockage found in learning during the literacy phase. For this reason, the work was developed through bibliographic research so that we had theoretical subsidies that extended the universe of investigation of the treatment given to the work of neuropsychopedagogists. Following the idea that guides the proposal of the National Curricular Parameters, all education committed to the exercise of citizenship needs to create conditions so that students can develop their competence and skills. The intention is to ascertain which skills and competencies such individuals have, so that a neuropsychopedagogical intervention that is most appropriate to their problem can be indicated. Understanding the purpose of the duties of the neuropsychopedagogue is a question that is necessary at this time.